Large Variability of Frequency and Type of Physical Therapy in Patients in the German Network for Systemic Sclerosis. Issue 8 (5th July 2020) - Belz, D.; Moinzadeh, P.; Riemekasten, G.; Henes, J.; Müller‐Ladner, U.; Blank, N.; Koetter, I.; Siegert, E.; Pfeiffer, C.; Schmalzing, M.; Zeidler, G.; Schmeiser, T.; et al.
Abstract : Objective: To determine the type and frequency of physical therapy (PT) prescribed by physicians for patients in the registry of the German Network for Systemic Sclerosis. Methods: The data for 4, 252 patients were analyzed using descriptive statistics, chi‐square tests, and odds ratios (ORs). Results: Overall, 37.4% of patients (1, 590 of 4, 252) received PT at the end of a yearly follow‐up. The most frequently used type of PT was lymphatic drainage (n = 1, 061, 36.8%), followed by exercise therapy (n = 1, 047, 36.3%) and heat therapy (n = 689, 23.9%). More than three‐fourths of treated patients (82%) received 1 or 2 different forms of PT simultaneously. The prescription of PT was associated with the extent of skin fibrosis as measured by the modified Rodnan skin thickness score (<10 [41.8% of patients], 11–20 [55.8% of patients], and >21 [63.9% of patients]; P < 0.001). Patients with musculoskeletal involvement (e.g., arthritis, muscle weakness, joint contractures, tendon friction rubs) had a higher chance of receiving PT than patients without these symptoms, with corresponding ORs ranging from 1.96 (95% confidence interval [95% CI] 1.69–2.28) for joint contractures to 3.83 (95% CI 2.89–5.08) for arthritis. When comparing the type of PT prescription across the initial and all follow‐up visits from 2003 to 2017, significant alterations with a decreasing frequency of patients receiving PT could be observed ( P = 0.001). Conclusion: To our knowledge, this is the first study reporting the use of PT in patients with systemic sclerosis (SSc) in a large cohort. Although SSc is characterized by considerable disability and restriction of motion, <40% of patients received PT.